The Ten Commandments of risk based process safety. Issue 3 (12th June 2015) - Rosen, Robert
<x xml:space="preserve">Abstract</x> There are many critical points for inclusion in a Risk Based Process Safety program. This paper focuses on ten of them. While a person could come up with many more, these are the most important in the author's experience. © 2015 American Institute of Chemical Engineers Process Saf Prog 34: 212–213, 2015